The book relations between the University of Lithuania and France - Lietuvninkaitė, Nijolė (Knygotyra, 1999)
The purpose of the article is to reveal the nature of the book relations between the University of Lithuania and France. These relations were a constituent part of the scientific, pedagogical, and cultural cooperation. The latter was developed between the University and various French scientific institutions and societies. It intensified in the second decade of the University’s work (1932-1940). The mutual cooperation had the greatest influence on the Faculty of Humanities. Notable French philologists and literati (R. Schmittlein, A. Prioult, and others) lectured there. The government of France supported the studies of the French language and literature. There were direct relations between the Library of the University and France. They became one of the sources of the book fund enrichment through the exchange of books and receiving them as gifts. The Library received donations of publications from the French government and its institutions, as well as from various publishers and private individuals. The book fund was enriched by about 2,000 publications, which influenced the studies of humanities. The most significant private gift was 294 publications from the personal library of the poet and diplomat of Lithuanian origin, Oskaras Milašius. Gifts and exchanges did not significantly impact the growth of the book fund of the Library. However, there are no doubts about their scientific and cultural value. A conclusion can be drawn that the book relations between the University of Lithuania and France grew together with the scientific and cultural cooperation. They were an effective contribution to the intellectual cooperation between the two countries—Lithuania and France.